PROGRESS IN CPA LEGISLATION. - Boyd, R. L. (The Accounting Review, 1944)
Abstract In June 1943 the Illinois legislature enacted a new CPA law to repeal and replace both the CPA law of 1903 and the public accountant law of 1927. Certain important features of this new law provide for freedom of interstate practice with control of out-of-state practitioners, eventual restriction of public practice to certified public accountants, recognition of general education beyond the high school level, and requirements for accountancy education of a collegiate grade. The Illinois public accountant law of 1927 provided for the licensing of practitioners and the restriction of practice, but it recognized out-of-state accountants only if their states recognized the Illinois license rather than the CPA certificates. Another feature of the 1943 Illinois CPA law is the provision for restriction of practice to certificate holders licensed by the state. Under this provision the State Department of Registration and Education will in the future license only individuals holding CPA certificates issued by the University of Illinois. The 1903 Illinois law contained the earliest statutory requirement of high school education for candidates. Administrative boards in New York and Pennsylvania had set up a requirement of high school education for candidates in an attempt to place certified public accountants on a professional par with attorneys and doctors, for whom similar requirements were then in effect.